Risk factors associated with multiple organ damage in childhood-onset systemic lupus erythematosus - Thanaporn Puengpipattrakul; Butsabong Lerkvaleekul; Kwanchai Pirojsakul; Soamarat Vilaiyuk (Frontiers Media S.A., 2023)
ObjectivePrevious studies have shown that approximately 39%-65% of patients with childhood-onset systemic lupus erythematosus (cSLE) have damage in at least one organ. Data on risk factors for organ damage in cSLE remain limited, especially in Asian populations. This study was conducted to evaluate the incidence of cSLE and identify the risk factors for accumulated organ damage in patients with cSLE.MethodsThis was a retrospective study. Patients aged <18 years who were diagnosed with cSLE between 2008 and 2020 were enrolled. Information on baseline characteristics, treatment, and disease activity assessed using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) was collected from diagnosis until the most recent visits were reviewed from medical records. Disease damage was measured using the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI).ResultsA total of 134 patients with a mean age at diagnosis of 11.2 ± 2.9 years were enrolled. The median duration of treatment was 4.7 (interquartile range 2.8-7.1) years. Forty patients (29.9%) had irreversible organ damage (SDI > 1) with an incidence rate of 5.7 events per 100 person-years. The most frequent type of organ damage was ocular (11.1%), followed by musculoskeletal (8.9%) and neurological (7.4%). High disease activity at diagnosis (SLEDAI-2K ≥ 12) (odds ratio [OR] 3.19, 95% confidence interval [CI] 1.32-7.68), infection (OR 3.73, 95% CI 1.60-8.67), and mycophenolate mofetil use (OR 3.62, 95% CI 1.45-9.03) were predictors of organ damage. The median time to disease damage in patients with SLEDAI-2K scores ≥12 at diagnosis was 6.5 years (95% CI 5.77-7.36; P = 0.004).ConclusionPhysicians should be aware of organ damage in patients with cSLE, particularly those with high disease activity at initial presentation, those who are receiving mycophenolate mofetil therapy, and those with an infection.